EFEKTIFITAS E-MODUL BERBASIS KUMON BERBANTUAN MOODLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MAHASISWA - Syita Fatih 'Adna; Nur Baiti Nasution; Gunawan Gunawan Gunawan (Universitas Pekalongan, 2022)
Lecturers of the Mathematics Education study program at Tidar University are required to use ELITA in online learning. ELITA is a learning media with a Moodle-based platform. Although the ELITA feature is complete, many lecturers are not optimal in using it. Lecturers only provide pdf material without considering the mastery of students' basic abilities. So we need a learning module that can emphasize the mastery of understanding mathematical concepts. In this study, a Kumon-based e-module with the help of Moodle was applied. The purpose of this study was to analyze the effectiveness of the Kumon-based e-module with the help of Moodle. The sample was taken by cluster random sampling, obtained by class 01 students in the odd semester probability subject for the 2021/2022 academic year. Prior to implementation, the validity of the Kumon-based e-module assisted by Moodle was analyzed. The e-module is declared to be very valid both in terms of material and media aspects. The research data was obtained through a student's mathematical concept understanding ability test. The final data were analyzed using the proportion test. Based on the results of the study, the Kumon-based e-module with the help of Moodle was effectively used in learning the Probability course on the ability to understand mathematical concepts of students.